2019
DOI: 10.1002/ejlt.201900084
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Approach to the Oxidation of Linseed Oil as Influenced by Fruit Peel and Seeds of Pomegranate

Abstract: The objective of this research is to analyze the kinetic parameters of linseed oil by treating it with pomegranate peel and seeds at 353, 368, and 383 K using Rancimat. There are no significant differences (p < 0.05) between the oxidative stability indices of samples containing pomegranate peel and pomegranate seeds. In addition, the indices pertaining to the oxidative stability of linseed oil increase in value as the concentrations of pomegranate peel and seeds increase. Apart from the pomegranate peel at 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
2
7
1
Order By: Relevance
“…For all studied oils, ΔH ++ were positive, confirming the endothermic nature of the lipid oxidation reaction previously reported for not flavored olive oils (Farhoosh et al, 2008;Farhoosh & Hoseini-Yazdi, 2014, Gharby et al, 2016Heidarpour & Farhoosh, 2018, Veloso et al, 2020. Besides, the ΔH ++ decreased significantly (P-value < 0.05), from 79.4 to 74.1 kJ mol − 1 , with the increase of EO level (from 0.0 to 0.4% EO, w/w), which is in agreement with the results of Mahalleh et al (2019) for flavored soybean oil and of Golmakani, Keramat, Darniyani, and Leila (2020) for flavored linseed oil, but contrary to the findings of Gülmez and Ş ahin (2019) for flavored hazelnut oils. The higher ΔH ++ values for the cv.…”
Section: Kinetic-thermodynamic Parameters Of Unflavored and Flavored Olive Oilssupporting
confidence: 90%
See 1 more Smart Citation
“…For all studied oils, ΔH ++ were positive, confirming the endothermic nature of the lipid oxidation reaction previously reported for not flavored olive oils (Farhoosh et al, 2008;Farhoosh & Hoseini-Yazdi, 2014, Gharby et al, 2016Heidarpour & Farhoosh, 2018, Veloso et al, 2020. Besides, the ΔH ++ decreased significantly (P-value < 0.05), from 79.4 to 74.1 kJ mol − 1 , with the increase of EO level (from 0.0 to 0.4% EO, w/w), which is in agreement with the results of Mahalleh et al (2019) for flavored soybean oil and of Golmakani, Keramat, Darniyani, and Leila (2020) for flavored linseed oil, but contrary to the findings of Gülmez and Ş ahin (2019) for flavored hazelnut oils. The higher ΔH ++ values for the cv.…”
Section: Kinetic-thermodynamic Parameters Of Unflavored and Flavored Olive Oilssupporting
confidence: 90%
“…Table 3 also shows the T C and Q 10 values calculated after linearization (determination coefficients, R 2 , varying between 0.9884 and 0.9982), being not observed a significant effect of EO flavoring level (Pvalue > 0.05), pointing out that no significant increase in the reaction rates could be attributed to a 10 • C rise. However, the literature reported a decreasing trend of the T C and Q 10 values of soybean or hazelnut oils flavored with catmint extract or with pomegranate peels and seeds (Golmakani, Keramat, & Leila, 2020;Mahalleh et al, 2019).…”
Section: Kinetic-thermodynamic Parameters Of Unflavored and Flavored Olive Oilsmentioning
confidence: 96%
“…In addition, linseed oil under oxygen-free atmosphere, e.g., N 2 (g) environment, did not react at all during 250 h indicating the significance of oxygen presence for the polymerization [ 52 ]. The oxidation rate of linseed oil agrees with Arrhenius law [ 48 , 82 , 83 ] as well as spoilage of some food products [ 9 , 78 , 84 ], therefore all the measurements were conducted under the same temperature, 27 °C, humidity and oxygen concentration.…”
Section: Methodsmentioning
confidence: 90%
“…For instance, Farhoosh et al, (2008) reported that the E a of soybean oil was higher than the olive oil, though it is obvious that the soybean oil has lower oxidation stability compared to olive oil. In another study, the E a for linseed oil (without antioxidant) was higher than linseed oil containing TBHQ (Golmakani et al, 2020). Nevertheless, the question that arises here is -how may theE a of a lipid system with lower oxidation resistance be higher than that of a lipid system with higher resistance?…”
Section: Revision On the Calculation Methods Of The Rate Constantmentioning
confidence: 79%